Making room for the extraeconomic: Ontology for contemporary critical urban inquiry. Issue 6 (2nd November 2019) - Harris, Keith
Abstract : This paper revisits the 2011 debate in City over the relationship between assemblage urbanism and critical urban theory. Rather than emphasizing the somewhat exaggerated cleavage between the two sides of the debate, it seeks to address some of the incisive critiques that Brenner, Madden, and Wachsmuth ([2011]. "Assemblage Urbanism and the Challenges of Critical Urban Theory." City 15 (2): 225–240) level against McFarlane's ([2011a]. "Assemblage and Critical Urbanism." City 15 (2): 204–224) thought experiment regarding what assemblage thinking might bring to critical urban theory by returning to Deleuze and Guattari's political philosophy. It both explores the lineage of the two central concepts defining Deleuze and Guattari's political philosophy—the 'state apparatus' and the 'war machine'—and uses aspects of the redevelopment of Seattle's South Lake Union neighborhood as case study to argue that their political theory is especially well-suited for understanding the interaction of economic and extraeconomic forces (specifically ethics and aesthetics) in contemporary urban development.